Tool Noun in Al-Qamoosi poetry A Study in the Semantics of the Conjugation Structure - Tayar Fadhil Hameed , Researcher; Salima Jabbar Ghanim , Prof. Dr. (lark, 2023)
There are various derivatives construction in Arabic in both form and meaning. One of those derivatives is Tool Noun which is a noun performing a verb, it has three standard forms, other than those is considered auditory. In this paper, we will shed light on this type of derivatives trying to discover function mechanisms and its meanings in the poetry of Sadiq Al-Qamoosi (1988 A.D). He was born in Najaf and wrote collection of poems that was collected and commented on by Mohamed Ridha Al-Qamoosi. Undoubtedly, poetry is different from any other form of speech; if language is a means of communication, poetry has its special rules and conditions, it is subjected in form and rhythm to restricted rules. Accordingly, any linguistic study and on any linguistic level that takes poetry as an applied domain, it should take into consideration those special poetic rules to clarify if there is a certain implication behind choosing it. We will clarify some of these uses of tool nouns in Al-Qamoosi poetry based on the effect of context in clarifying tge implications of function and use of tool nouns